Faktor Faktor Yang Mempengaruhi Firm Value Pada Perusahaan Consumer Cyclicals Dan Consumer Non-Cyclicals - Putri, Cilvia Cahyani; Nugroho, Vidyarto (Jurnal Paradigma Akuntansi, 2025)
This article discusses research on the effect of sales growth, firm size, profitability, and liquidity on firm value in the consumer cyclical and non-cyclical sectors listed on the Indonesia Stock Exchange 2020-2022. The method used in this research is a quantitative descriptive approach. Company financial reports on the IDX are used as the primary research data source in the consumer cyclical and consumer non-cyclical categories. Testing using the F test yields information that there is an influence from sales growth, firm size, profitability, and liquidity on firm value/company value. Testing with the t-test yields information that sales growth positively affects firm value. A significant positive effect is shown by firm size on firm value, while profitability shows a significant positive effect. Meanwhile, the negative effect is not significant, as indicated by liquidity on firm value.